2012
DOI: 10.1016/j.biopsych.2011.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony of Corticostriatal-Midbrain Activation Enables Normal Inhibitory Control and Conflict Processing in Recovering Alcoholic Men

Abstract: Background Alcohol dependence is associated with inhibitory control deficits, possibly related to abnormalities in frontoparietal cortical and midbrain function and connectivity. Methods We examined functional connectivity and microstructural fiber integrity between frontoparietal and midbrain structures using a Stroop Match-to-Sample task with functional MRI and diffusion tensor imaging in 18 alcoholics and 17 controls. Manipulation of color cues and response repetition sequences modulated cognitive demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 69 publications
(73 reference statements)
8
60
0
Order By: Relevance
“…As the PCC is part of DMN, which is synchronized with low-frequency oscillations in some brain regions during the resting-state, it is important for attention and self-monitoring as it involves cognitive functions associated with the coupling of executive control and the ability to disengage from the DMN (Fox and Raichle, 2007). Several studies reported functional abnormality IGD or AUD in the PCC, including increased ReHo (Liu et al, 2010) and failing to exhibit task-induced deactivation (Schulte et al, 2012). Chanraud et al (2011Chanraud et al ( , 2012 supported that difference in brain activity and in the functional synchrony between brain regions may be compensatory and bestow resources for task processing in alcoholism during the resting-state.…”
Section: Discussionmentioning
confidence: 97%
“…As the PCC is part of DMN, which is synchronized with low-frequency oscillations in some brain regions during the resting-state, it is important for attention and self-monitoring as it involves cognitive functions associated with the coupling of executive control and the ability to disengage from the DMN (Fox and Raichle, 2007). Several studies reported functional abnormality IGD or AUD in the PCC, including increased ReHo (Liu et al, 2010) and failing to exhibit task-induced deactivation (Schulte et al, 2012). Chanraud et al (2011Chanraud et al ( , 2012 supported that difference in brain activity and in the functional synchrony between brain regions may be compensatory and bestow resources for task processing in alcoholism during the resting-state.…”
Section: Discussionmentioning
confidence: 97%
“…During a task engaging executive functions (ie, Stroop task), Schulte, M€ uller-Oehring, Sullivan, and Pfefferbaum (2012) observed that connectivity of the middle cingulate cortex (MCC) was modified in alcoholics compared to controls. For this experiment, the Stroop effect was defined as the difference in RT between incongruent and congruent stimuli.…”
Section: Functional Connectivitymentioning
confidence: 99%
“…These findings show a double dissociation of anterior and posterior cortical systems engaging in different types of control for perceptually driven and action-driven conflict resolution and showed that appropriate engagement of topdown control was disrupted in the healthy elderly (Schulte et al, 2009). This paradigm was also successful in identifying disruption of top-down regulation of inhibition used by controls and evidenced as medial prefrontal-posterior cingulate activation synchrony in contrast with recovering alcoholics who invoked a bottom-up strategy marked by greater midbrain-orbitofrontal connectivity than controls (Schulte et al, 2012).…”
Section: Frontostriatal Circuitrymentioning
confidence: 86%
“…A common finding in task-activated paradigms tapping response inhibition has been weaker connectivity in frontostriatal networks in alcoholics compared with controls (Courtney, Ghahremani, & Ray, 2013). In some instances, weaker connectivity was associated with a composite measure of alcoholism severity (Courtney et al, 2013), greater amounts of alcohol consumed over a lifetime (Schulte, Müller-Oehring, Sullivan, & Pfefferbaum, 2012), and length of sobriety (Dresler et al, 2011).…”
Section: Frontostriatal Circuitrymentioning
confidence: 98%
See 1 more Smart Citation